Seasonality and interindividual variation in mandrill feeding ecology revealed by stable isotope analyses of hair and blood. Issue 12 (19th October 2020) - Oelze, Vicky M.; Percher, Alice M.; Nsi Akoué, Gontran; El Ksabi, Nory; Willaume, Eric; Charpentier, Marie J. E.
Abstract: Mandrills are large‐bodied terrestrial forest primates living in particularly large social groups of several hundred individuals. Following these groups in the wild to assess differences in diet over time as well as among individuals is demanding. We here use isotope analyses in blood and hair obtained during repeated captures of 43 identified free‐ranging mandrills ( Mandrillus sphinx ) from Southern Gabon, to test how dietary variation relates to the season as well as an individual's age and sex. We measured the stable carbon (δ 13 C‰) and nitrogen (δ 15 N‰) isotope ratios in 46 blood and 214 hair section samples as well as from a small selection of mandrill foods ( n = 24). We found some seasonal isotopic effects, with lower δ 13 C values but higher δ 15 N values observed during the highly competitive long dry season compared to the fruit‐rich long rainy season. Variation in δ 13 C was further predicted by individual age, with higher δ 13 C values generally found in younger individuals suggesting that they may consume more high canopy fruit than older individuals, or that older individuals consume more low canopy foliage. The best predictor for δ 15 N values was the interaction between age and sex, with mature and reproductively active males revealing the highest δ 15 N values, despite the observation that males consume substantially less animal food items than females. We interpret high δ 15 N values in these mature male mandrill blood and hair sections to be the result of nutritional stress associated with intense male–male competition, particularly during mating season. This is the first study showing isotopic evidence for nutritional stress in a free‐ranging primate species and may spark further investigations into male mandrill diet and energy balance. Abstract : High δ15N values in adult male mandrills.